Money Matters: Investigating Mental Accounting Proxies in Indonesia through Behavioral Accounting Lens - Ardimansyah, Ardimansyah; Putri, Della Arnita; Wulandari, Hesty Safitri; Haryono, Haryono; Yunita, Khristina (Universitas Negeri Yogyakarta, 2023)
ABSTRACTThe main objective of this research is to provide a historical context for the development of mental accounting studies in Indonesia, specifically by analyzing how the field of mental accounting has evolved in Indonesia, with a focus on the topics covered in the articles published in accredited accounting journals. Among the 72 accredited accounting journals and those indexed in the Science and Technology Index (SINTA) ranking second and third, a total of 8 articles representing accounting research in Indonesia were identified. This study analyzes the development of the mental accounting field using the charting the field approach. The articles or journals are classified in this research according to research topics, research methodologies, and publication years. Based on the mapping conducted, articles with mental accounting topics were predominantly based on quantitative methods. Research on mental accounting topics needs to be continuously developed given its importance in everyday implementation.Keywords: Accredited Journal, Accounting Research, Mental Accounting.ABSTRAKTujuan utama dari penelitian ini adalah untuk memberikan konteks sejarah bagi perkembangan kajian mental accounting di Indonesia secara khusus menganalisis bagaimana bidang akuntansi mental telah berkembang dari waktu ke waktu di Indonesia dengan fokus pada topik artikel tersebut yang telah diterbitkan dalam jurnal akuntansi terakreditasi. Di antara 72 jurnal akuntansi terakreditasi dan jurnal akuntansi yang terindeks Science and Technology Index (SINTA) dengan peringkat kedua dan tiga besar, yang memuat total 8 (delapan) artikel yang mewakili penelitian akuntansi Indonesia. Studi ini menganalisis bagaimana perkembangan bidang akuntansi mental melalui penggunaan pendekatan charting the field. Artikel atau jurnal diklasifikasikan dalam penelitian ini sesuai dengan topik penelitian, metodologi penelitian, dan tahun publikasi. Berdasarkan hasil pemetaan yang dilakukan, artikel dengan topik mental accounting didominasi oleh metode kuantitatif. Penelitian dengan topik mental accounting harus terus dikembangkan mengingat pentingnya dalam implementasi sehari-hari.Kata Kunci: Jurnal Terakreditasi, Riset Akuntansi, Akuntansi Mental